Hubungan Komunikasi Interpersonal Tutor Dengan Hasil Belajar Paket B Kelas IX Pada Matapelajaran IPS PKBM Farilla Ilmi Kota Padang - Ningsih, Yulia Widiya; Ismaniar, Ismaniar (Jurnal Family Education, 2024)
ABSTRACT This research is motivated by the low academic performance of the Paket B learners, as evidenced by their report card grades which are still below the Minimum Completeness Criteria (KKM), with the KKM set at 80. It is suspected that the low academic performance of Paket B learners is related to the less effective interpersonal communication between tutors and students. This study is a quantitative correlational research. The population of this research consists of all learners in Paket B, Grade IX at PKBM Farilla Ilmi Padang, totaling 45 learners for the 2022/2023 academic year. The sampling technique used is cluster random sampling, which involves randomly selecting a sample of 32 individuals, or 71% of the 45 participants. The data collection technique employed is a questionnaire, with the research instrument being a questionnaire as well. Data analysis is performed using percentage formulas. The research findings are as follows: 1) The interpersonal communication of tutors with learners in the IPS subject at PKBM Farilla Ilmi is categorized as good; 2) The academic performance of Paket B learners in Grade IX in the IPS subject at PKBM Farilla Ilmi is categorized as poor; 3) There is no relationship between the interpersonal communication of tutors and the academic performance of Paket B learners in Grade IX in the IPS subject at PKBM Farilla Ilmi.